Ten‐year pattern of red blood cell use in the North of England. Issue 3 (15th July 2012) - Tinegate, Hazel; Chattree, Shikha; Iqbal, Adil; Plews, Dianne; Whitehead, Jeni; Wallis, Jonathan P.; ,
<x xml:space="preserve">Abstract</x> BACKGROUND: An understanding of current and changing patterns of red blood cell (RBC) use will help predict future demands and aid future planning for transfusion services. It can also highlight areas where efforts to optimize RBC use are most likely to be productive. STUDY DESIGN AND METHODS: Surveys were conducted in two 14‐day periods of all RBC transfusions in a geographic region of England supplied by a single blood center. Data collection was prospective and used preprinted paper forms. Results were compared with two previous studies covering a period of 10 years. RESULTS: The clinical fate of 8025 units of RBCs was recorded consistent with data on more than 99% of units issued and transfused during the survey period. The overall RBC transfusion rate has decreased from 45.5 to 36 units per 100, 000 population from 1999 and 2009. Twenty‐nine percent were used for surgical indications indicating a further decrease in surgical use compared to previous surveys. This decrease was limited solely to recipients of 50 to 80 years of age. Use for medical and obstetric/gynecologic indications has not changed significantly over 10 years. CONCLUSION: Further decreases in surgical RBC use may be achievable but the aging population is likely to demand more blood for nonsurgical indications and efforts should be directed to optimizing use in these recipients. Comparative data on transfusion rates between regions or countries may be a useful tool for improving blood use.